Application of e-procurement technologies for selecting suppliers of agro-based SMEs in Malaysia - Kamarulzaman, Nitty Hirawaty; Mohamed, Zainal Abidin (Faculty of Economics and Management, Universiti Putra Malaysia, 2013)
E-procurement is one aspect in supply management that has become popular among companies in Malaysia. There is an argument whether adopting e-procurement technology is a strategic choice for companies’ purchasing strategies. The objectives of this study are to investigate factors that influence the application of e-procurement technologies in selecting potential suppliers of agro-based SMEs in Malaysia and to determine whether these SMEs have the intention to increase the application of e-procurement in selecting their suppliers. An online survey was carried out and only 190 responses (63.3%) were received from selected agro-based SMEs. Statistical analyses such as descriptive analysis, factor analysis and logistic regression analysis were used to analyse the data. The results revealed selection efficiency, security and legal environment, commitment, delivery acceleration, cost and quality as the factors related to the intention of SMEs to increase the application of e-procurement. A vigorous use of e-procurement and strong support from the top management by providing sufficient e-procurement resources to be utilized in agro-based SMEs are a few among many relevant implications discussed in this paper.